Association Between Fear of COVID-19 and Emotional Distress in Nurses With Mediating Role of Socio-Demographic Features - Abid, Mueen; Riaz, Maryam; Bano, Zaqia; Parveen, Tahira; Umar Fayyaz, Muhammad; Sadia Qureshi, Halima (Frontiers in Psychology, 2021)
To determine the predictive association between fear of COVID-19 and emotional distress (depression, anxiety & stress) in frontline and non-frontline nurses. To explore mediating role of socio-demographic features. Methods: Correlational cross sectional research design was implied. All the 500 on duty male and female frontline and non-frontline nurses were included from 5 major hospital of Gujrat (Aziz Bhatti Shaheed Hospital, City Hospital, Doctors Hospital, Akram Hospital & Gujrat Hospital). Fear of COVID-19 scale and Urdu version of the DASS-21 scale was used to measure variables of interest. Descriptive statistics, structural equation modeling (SEM), linear regression and T-test were carried out by using SPSS 21. Result: Structural equation modeling revealed a significant predictive link between fear of CONID-19 and depression, anxiety and stress (goodness of model fit; NFI = .93, GFI = .914, AGFI = .93, CFI = .936 & IFI = .936). Furthermore, a significant mediating effect of certain demographic features was discovered by structural equation modeling (CMIN/DF = 1.11, NFI = .94, TLI = .98, GFI = .08, AGFI = .93, RMSEA = .029, CFI = .99 and IFI = .99). Results of linear regression analysis also revealed a momentous predictive association between fear of COVID-19 and emotional distress (R = .860). In comparative analysis, results of t-test explored statistical significant difference in fear of COVID-19 and emotional distress between frontline (mean = 25.775, 36.147 & SD = 1.75, 2.23) and non-frontline nurses (mean = 21.702, 27.353 & SD = 4.607, 10.212), t (130) =7.111, 6.92. Conclusion: Managing the mediating effect of demographic characteristics and reducing the fear of COVID-19 can help nurses to overcome the emotional distress such as depression, anxiety and stress. Further, this will increase the productivity of nurses.